(untitled) (Global Journal of Science Frontier Research, 2014)
In this study, using differential transform method second order complex differential equation system was solved. Firstly we seperated real and imaginer parts these equations system. Thus from two unknown equation system four equality was obtained. Later using two dimensional differential transform we obtained real and imaginer parts of solutions.